Implementing Skin-to-Skin Care in the Operating Room After Cesarean Birth. Issue 4 (July 2015) - Sundin, Courtney Stanley; Mazac, Lauren Bradham
Abstract: Background: After vaginal birth, newborns who have been skin-to-skin (STS) with their mother have greater temperature and glucose stability and higher exclusive breastfeeding rates at discharge. There are minimal data about STS in the operating room (OR) after cesarean birth. Although implementing STS in the OR can be challenging, it may promote positive maternal and infant outcomes. Purpose: The purpose of this quality improvement project was to evaluate maternal satisfaction and maternal perception of pain when babies were placed STS immediately after cesarean birth in the OR. Study Design and Methods: This quality improvement project was conducted at Baylor All Saints Medical Center-Andrews Women's Hospital, an urban, nonprofit, private hospital with an average of 5, 000 births per year. Over a 90-day period, all women having cesarean birth were evaluated for two outcomes, maternal birth experience and pain perception during surgery. Following scheduled repeat cesarean, satisfaction of the birth experience was compared to the previous birth experience. Pain control during surgery of women having cesarean birth with and without STS was evaluated. Postpartum interviews with the new mothers and review of their anesthesia records were used to determine project findings. Results: Maternal satisfaction was higher and maternal perception of pain was lower for women who experienced STS in the OR when compared to women where STS was not performed. Clinical Implications: Babies can be placed STS in the OR with positive implications for mothers' satisfaction with the birth experience and their perception of pain during the surgical procedure. Infant safety should be supported by a nurse with the mother and baby during the STS process. Abstract : Placing the baby skin to skin with the mother in the OR after cesarean birth may have positive implications for maternal satisfaction with the birth experience and maternal perceptions of pain during the surgical procedure. Infant safety should be supported by a nurse with the mother and baby during the skin to skin process.